A teacher's resources for teaching the Formative Itinerary of Financial, Tax, and Entrepreneurial Education: an analysis in light of the Documentary Approach to Didactics theory (Research, Society and Development, 2022)
This study aims to analyze the development of teaching in the context of the formative itinerary of Financial, Tax and Entrepreneurial Education, from the mapping of the teacher's resource system. The research has a qualitative approach with the design of a case study and was anchored in the Documentary Approach to Didactics. The participant of the study is a high school teacher of a public school, located in the east zone of Manaus and the data were collected from logbook, questionnaires, interviews and filming. In this study, it was evident the dynamic character of the Teacher Resource System, in the process of creating and adapting resources and it can be seen that considering the student as the protagonist of the process and use of contextualized tasks as beliefs in action present in the teacher's scheme for teaching Financial, Tax and Entrepreneurship Education.